Present status and future direction in feed resources and nutrition research targeted for wheat based crop-livestock production system in Ethiopia - Bediye, S.; Assefa, G.; Tedla, A.; Fekadu, D. (International Maize and Wheat Improvement Center, 2001)
Mixed crop-lvestock production system is the major agricultural production system in Ethiopia with a wide array of Development challenges and opportunities. One of the key challenge in improving the agricultural productivity of the system is feed scarcity and undernutrition. The major basal feed resources in wheat based farming systems are native pasture, crop residue and aftermath grazing. The contribution of each feed resource to the total feed varies from area to area based on cropping intensity. In the most intensively cultivated areas, crop residues and aftermath grazing account for about 60-70% of the basal diet suggesting wheat straw to be the dominant feed in wheat based farming system. The current scenario in feed availability in wheat based crop-livestock production systems suggest basal feed of less than 1.6 ton/TLU per annum. Local research efforts on nutritive value of wheat straw were limited to characterization work and few animal response studies. Potential to upgrade nutritive value of wheat straw either through treatments and or supplementation is elaborated using data generated in similar environments. The role of forage legumes in improving the feed resource base and farming system are highlighted and research findings in integration strategies reviewed. Future research directions focus on upgrading the nutritive value of wheat straw and the use of forage legumes in the farming system.